2011
DOI: 10.1143/jpsjs.80sa.sa030
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of the Filled Skutterudite ThPt4Ge12Investigated by Muon Spin Rotation

Abstract: The superconducting state of the filled skutterudite ThPt 4 Ge 12 has been investigated by the zero-field longitudinal and transverse-field muon spin rotation technique. The deduced temperature dependence of the muon spin depolarization rate, σ s , at 0.04 T has been analyzed in terms of a phenomenological powerlaw behavior and a model appropriate for clean limit superconductors. The estimated effective Fermi temperature T F = 87 K has been compared by means of the Uemura plot with those derived for other supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…These features suggest the presence of antiferromagnetic spin fluctuations and hint at an unconventional character of the superconducting state that possibly emerges in the proximity of a quantum critical point instability, alike in the related HF superconductors CeT In 5 and Ce 2 T In 8 with T = Co, Rh and Ir [4]. The latter hypothesis seems supported by recently obtained muon spin rotation spectroscopy and inelastic neutron scattering data [5], which clearly evidence magnetically-driven superconducting behavior in Ce 2 PdIn 8 , even if long-range AF order is actually absent as an intrinsic property of this compound.…”
supporting
confidence: 53%
“…These features suggest the presence of antiferromagnetic spin fluctuations and hint at an unconventional character of the superconducting state that possibly emerges in the proximity of a quantum critical point instability, alike in the related HF superconductors CeT In 5 and Ce 2 T In 8 with T = Co, Rh and Ir [4]. The latter hypothesis seems supported by recently obtained muon spin rotation spectroscopy and inelastic neutron scattering data [5], which clearly evidence magnetically-driven superconducting behavior in Ce 2 PdIn 8 , even if long-range AF order is actually absent as an intrinsic property of this compound.…”
supporting
confidence: 53%
“…These features suggest the presence of antiferromagnetic spin fluctuations and hint at an unconventional character of the superconducting state that possibly emerges in the proximity of a quantum critical point instability, alike in the related HF superconductors CeT In 5 and Ce 2 T In 8 with T = Co, Rh and Ir [4]. The latter hypothesis seems supported by recently obtained muon spin rotation spectroscopy and inelastic neutron scattering data [5], which clearly evidence magnetically-driven superconducting behavior in Ce 2 PdIn 8 , even if long-range AF order is actually absent as an intrinsic property of this compound. …”
mentioning
confidence: 60%
“…Non-Fermi-liquid behavior was observed in both macroscopic [6-10] and microscopic [11,12] measurements at low temperature, implying that Ce 2 PdIn 8 is located very close to a QCP. It was further suggested that a twodimensional (2D) SDW-type QCP is induced by magnetic field near the upper critical field, H c2 ≈ 2 T [9].…”
mentioning
confidence: 99%